Methodological problems of land use planning locally in terms of new land relations and decentralization of power - Kapinos, N. (Land Management, Cadastre and Land Monitoring, 2017)
Summary Fundamental changes of land relations that have been established for the period of land reform in the independent Ukraine and the new socio-economic and environmental problems identified new character and content of the land. During the land reform in Ukraine to land management encountered new challenges that focus on the implementation of land policy and land relations fundamental change. Accordingly, to land management faces new challenges.Today for events to decentralize power facilities, new land - the territory united local communities should determine for whom the prospect of organizing the use and protection of land and other natural resources. However, the current land law the answer to this problem does not. Instead, normalization is an attempt to issues related to improving the quality of drafting documentation spatial planning (urban planning documents) establish procedures for integrated development plans of local communities, the introduction of rules regulating local area to establish procedures for planning, construction and other use areas and about objects, improving public hearings to address public interests and relieve tension in the planning and construction of the territories.However, planning documentation does not solve the problems of perspective development of the organization use and protection of land and other natural resources. There is a need to distinguish between objects of regional urban planning and land management. This is because the urban planning regulations covering mainly two categories of land (settlements, industry, transport, communications and other purposes), not including agricultural land, which houses objects of capital construction. However, they make up for Ukraine just 4.2% of the total area. For the remaining seven categories of land (agricultural land, forest and water resources, conservation, recreation, recreational purposes) land use planning and their protection should be based on land documents.For a reasonable solution for the sustainable development of land use in rural areas must both technologically interconnected circuits develop spatial planning, land management schemes and schemes establishing an ecological network within the area councils.In this regard, we propose to change the ideology (concept), spatial planning for land development, directing it to priority land use tasks as part of the documentation for land management on the territory of the councils, including the consolidated territorial communities, which needs to assess the land resource and other natural resource potential of the territory, to reconcile and harmonize territorial and land-property interests of the state and territorial communities, citizens and businesses, to give proposals for improving local systems and land use patterns; to establish a balanced use of the properties of the earth as a natural object, natural resource and real estate.Keywords: planning of land use, land management at the local level, city planning and land use documentation.